2021
DOI: 10.1155/2021/5513679
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network-Based Deep Learning Model for COVID-19 Patient Detection Using X-Ray Chest Images

Abstract: The world is experiencing an unprecedented crisis due to the coronavirus disease (COVID-19) outbreak that has affected nearly 216 countries and territories across the globe. Since the pandemic outbreak, there is a growing interest in computational model-based diagnostic technologies to support the screening and diagnosis of COVID-19 cases using medical imaging such as chest X-ray (CXR) scans. It is discovered in initial studies that patients infected with COVID-19 show abnormalities in their CXR images that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Shorfuzzaman et al [ 35 ] discussed a novel convolutional neural network- (CNN-) based deep learning blend structure employing the transfer learning idea. The proposed model accomplished an accuracy of 95.49%.…”
Section: Related Workmentioning
confidence: 99%
“…Shorfuzzaman et al [ 35 ] discussed a novel convolutional neural network- (CNN-) based deep learning blend structure employing the transfer learning idea. The proposed model accomplished an accuracy of 95.49%.…”
Section: Related Workmentioning
confidence: 99%
“…t-SNE [53] is an effective method of scaling down high-dimensional data to explore the distribution of features generated by models [54]: Suppose X is a vector containing all samples, and Y is a target vector of a low-dimensional representation of X. P j | i is a conditional probability in the original high-dimensional space to describe the similarity of data point x j to data point x i [53], as shown in Eq. ( 14):…”
Section: T-snementioning
confidence: 99%
“…The experimental results showed that the weighted average accuracies for the DLM according to CT, MRI, and X-ray are 85%, 86%, and 94% respectively. As presented in [17] , a new Covid-19 detection model called Convolutional Neural Network-based Deep Learning (CNN-DL) was introduced to provide accurate diagnosis by using Chest X-Ray (CXR) images. CNN-DL model used the average of the parameters’ weights from many models fitted into a single model to extract features from images.…”
Section: Related Workmentioning
confidence: 99%